PERBEDAAN ZONA HAMBAT PERTUMBUHAN SALMONELLA TYPHI PADA BERBAGAI KONSENTRASI REBUSAN DAUN MIMBA SECARA IN VITRO - igede sudarmanto (Poltekkes Kemenkes Denpasar, 2022)
Background Typhoid fever is one kind of typhoidal species group caused by infection of Salmonella Typhi. The general therapy of Salmonella Typhi is giving antibiotic. But giving it in the wrong dose can cause resistance of this bacteria. So, some people move to use traditional medicine to pretend the infection. One of plant that can use as alternative medicine is Azadirachta indica or neem. Neem leaf contain some substance such as quercetin and tannin that can use as antimicrobial.Objective to know about the effect of differences concentration of neem leaf boiled water on growth of Salmonella Typhi.Method The method of this research is true experiment with posttest only control design.Result There is zero zone of inhibition on concentration 20%, on 40% concentration is 4,9 mm of inhibition zone, on 60% is 7,8 mm of inhibition zone, on 80% is 9,1 mm of inhibition zone and on 100% is 11,1 mm of inhibition zone. The probability result testing by Anova is 0,000 0,05.Conclusion of this research is there are difference growth of Salmonella Typhi on different concentrate of neem leaf boiled water with in vitro inhibitionKeywords: neem leaf, Salmonella Typhi, inhibition